Agenda expose a media content management analysis of charm radio news and commentary programs - Alberca, Feliz F.
A Media Documented Analysis is a new approach determining how media content, which is the message, is created and even controlled by the management who runs a media organization. Using Agenda Setting Theory and Framing, AGENDA EXPOSE aimed to determine the content selection process of ho a public radio station conceptualizes their new and commentary programs. The analysis also identified the agenda of the management and how it is reflected in the program of the station. A 3-phase methodology was used in the study. The Familiarity Process, Qualitative Interview, and Interpretive Textual Analysis, data Analysis was contextualized with the radio station?s organizational structure and organization goals. Results of the analysis found a new dynamics on how the management selects the content of their news and commentary. A route was formulated and pattered according to the results ? the Selection route. The pattern showed the selection process and the agenda of the radio station management, and highlighted the different factors considered as underlying forces affecting media content. AGENDA EXPOSE validated that content is subject to sub-selection factors before it is actually transmitted to an audience. The Selection Route is considered as the emerging trend on how news and commentary content of a public radio station is created.